Primary glioblastoma multiforme of cerebellum: a case report and review of literature - Kluska, Adam; Tracz, Natalia; Loga, Karolina; Papis-Ubych, Anna; Fijuth, Jacek; Gottwald, Leszek (Medycyna Paliatywna/Palliative Medicine, 2020)
The most common primary malignant brain tumour in adults is glioblastoma multiforme (GBM), classified as grade IV glioma. GBM is the most aggressive of astrocytic gliomas, considered to be an incurable disease, with median survival of only 15 months when treated with surgery in combination with concomitant chemoradiotherapy. Most of GBM lesions are localised supratentorially, and all available guidelines about treatment of GBM refer to those tumours. Tumours in the infratentorial area are rarely suspected to be GBM; however, about 0.4-3.4% of GBM occur in the cerebellum. The rarity of cerebellar GBM means that pathogenesis, treatment, and prognosis in such cases are still not well defined. We report a case of a 46-year-old patient with primary cerebellar GBM treated in our centre.